2022
DOI: 10.1055/a-1980-8852
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition of Both Waist Circumference and Hip Circumference Increased the Risk of Venous Thromboembolism

Abstract: Background: Obesity, especially abdominal obesity, is an independent indicator of increased cardiovascular risk. Observational studies have shown an observational association between obesity and venous thromboembolism (VTE). As a type of VTE, pulmonary embolism (PE) is also associated with obesity. But it is unclear whether the observed associations are causal or caused by confounding bias or reverse causality. Methods: We performed a two-sample by obtaining the exposure data set of WC and HC from the Neale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Emerging research also explores the nuanced impact of body mass distribution on this condition, highlighting complexities beyond overall body weight. Wang et al 46 investigated the link between waist circumference and hip circumference with VTE, and particularly PE . They provided insights into visceral fat mass distribution as an independent risk factor for VTE.…”
Section: Weightmentioning
confidence: 99%
“…Emerging research also explores the nuanced impact of body mass distribution on this condition, highlighting complexities beyond overall body weight. Wang et al 46 investigated the link between waist circumference and hip circumference with VTE, and particularly PE . They provided insights into visceral fat mass distribution as an independent risk factor for VTE.…”
Section: Weightmentioning
confidence: 99%
“…1 Even in this journal there has been much interest in the epidemiology, prognosis, and risk factors for VTE, as well as the pathophysiological mechanisms underlying the propensity to develop this common condition. [2][3][4][5][6][7] Pregnancy is an important risk factor for VTE. Several previous studies reported the incidence of pregnancy-associated VTE (PA-VTE) for Western population.…”
mentioning
confidence: 99%
“…1 Even in this journal there has been much interest in the epidemiology, prognosis, and risk factors for VTE, as well as the pathophysiological mechanisms underlying the propensity to develop this common condition. 2 3 4 5 6 7…”
mentioning
confidence: 99%
“…1 Lifetime estimated risk of VTE in the United States is 8.1%, notably higher in black persons. Other important risk factors for developing VTE include obesity, 2 postsurgical populations, 3 recently hospitalized, cancer, 4 and those with sleep apnea. 5 Recent focus has included the associations of VTE to pregnancy and family history in women of childbearing age 6 7 as well as those with assisted reproductive technology.…”
mentioning
confidence: 99%